Adsorption characteristics of 4-hydroxy-3-aminophenylarsonic acid (HAPA) onto anaerobic granular sludge. Issue 44 (19th September 2016) - Li, Jun-Chao; Yuan, Shou-Jun; Wang, Wei; Ji, Feng; Hu, Zhen-Hu
Abstract: Four-hydroxy-3-aminophenylarsonic acid (HAPA) is the degradation product of 3-nitro-4-hydroxyphenylarsonic acid (roxarsone, a widely used organoarsenic additive in animal feed) under anaerobic conditions. HAPA is highly water soluble and resistant to degradation by anaerobic micro-organisms. In this study, the effect of initial concentration, temperature, pH, ionic strength, and interferential ions on the adsorption of HAPA onto anaerobic granular sludge (AGS) was investigated using batch adsorption experiments. The results showed that equilibrium state of the adsorption was reached at about 10 h. The kinetics analysis indicated that the adsorption process followed a pseudo-second-order model and intra-particle diffusion was the rate-limiting step. The adsorption mechanisms could be explained by the Freundlich and D–R isotherm models. The maximum adsorption capacity of HAPA onto AGS was 12.57, 25.05, and 26.31 mg/g at 15, 25, and 35°C, respectively. pH, ionic strength, and phosphate ions had obvious negative effect on the HAPA adsorption onto AGS. Thermodynamics analysis confirmed that the adsorption of HAPA onto AGS was an endothermic and spontaneous process. The results obtained from this study will improve the understanding to the adsorption characteristics of HAPA onto AGS and the fate of roxarsone in anaerobic sludge reactor.